ECONOMIC ANALYSIS OF DIFFERENT HYDRAULIC SPRAYERS USED IN SUGARCANE (Saccharum spp.) - Santos,Neisvaldo B. dos (2019)
ABSTRACT Brazil is the largest sugarcane producer worldwide. In mills, sugarcane crops are sprayed with agrochemicals using self-propelled, tractor-driven, and aerial hydraulic sprayers. As sugarcane spraying is regularly performed over extensive areas, the machinery to be used should be planned and dimensioned to ensure timely operations without overloading and at lower costs. Therefore, the current study aimed to analyze the operational and economic performances of different hydraulic sprayers to perform sugarcane crop control. As long as meeting our goal in field conditions would be difficult, we opted to develop a computational model, named as “TratoCana”, using a spreadsheet and programming language. The model was used to assess economic and operational factors by generating scenarios and analyzing probable routine errors. In short, the results evidenced that initial value and operation speed are factors with the strongest impact on the costs of self-propelled sprayers and tractor-sprayer sets. Yet, the aerial application was mostly affected by fuel costs and crop row lengths. Moreover, the larger the spray tank volume, the lower the costs.